The Structure of the Permanent Job Wage Premium: Evidence from Europe - Lawrence Kahn (Center for Economic Studies and ifo Institute (CESifo), 2013)
Using longitudinal data on individuals from the European Community Household Panel for thirteen countries during 1995-2001, I investigate the wage premium for permanent jobs relative to temporary jobs. For men, the wage premium for a permanent job is lower for older workers and native born workers, the latter effect being especially strong relative to those born outside the EU; for women, the permanent job wage premium is lower for older workers and those with longer job tenure. These findings suggest that the gain to employment in permanent jobs is higher for those with less experience in the domestic labor market.
Keywords: J31; J42; 330; wage structure; segmented labor markets; temporary jobs